Impact Evaluation of School Feeding Programs in Lao PDR - Buttenheim, Alison (Taylor and Francis, 2013)
Despite the popularity and widespread implementation of school feeding programmes, evidence of their impact on school participation and nutritional status is mixed. In this study we evaluate feeding programmes in three districts of the Lao People's Democratic Republic. Feeding modalities included on-site feeding, take-home rations, and a combined modality. District-level implementation of the intervention sites and selective take-up presented considerable evaluation challenges. To address these, we use difference-in-difference estimators with propensity-score weighting to construct plausible counterfactuals. We find minimal evidence that school feeding increased enrolment or improved nutritional status. Several robustness checks and possible explanations for null findings are presented.